ASSESSMENT OF BALL VALVE CLOSING IN WATER HAMMER EVENT VIA VIDEO PROCESSING METHOD - Kistak, C.; Eren, H. (Acad Sci Czech Republic, Inst Thermomechanics, 2016)
Water hammer event suddenly emerges as a result of instantly stopping or beginning the water flow through installation components and pipelines and is seen frequently in water installations. The waves emerging as a result of water hammer may lead to fractions and deformations by spreading throughout the installation. Valves and pumps are the main components of the most basic water installment schema, and are seen as the components that most frequently lead to water hammer in starting and stopping the water flow. In this study, for 3 flow velocities in a simple installment setting containing the main installment components, the event of closure of a ball valve with pneumatic actuator was examined experimentally via video processing method, and the effects of flow velocity on water hammer were investigated by visualizing the flow.
22nd International Conference on Engineering Mechanics -- MAY 09-12, 2016 -- Svratka, CZECH REPUBLIC
Keywords: Water hammer; Hydraulic shock; Video processing; Ball valve; Valve closing